The Impact of Written Corrective Feedback on Enhancing Second Language Writing Skills: A Comprehensive Review - Tiantian Guo (Ilmu Inovasi Nusantara, 2023)
This review explores the dynamic landscape of written corrective feedback (WCF) in the context of second language (L2) writing, aiming to provide a comprehensive understanding of its influence on language proficiency. Examining various typologies of WCF, including direct and indirect approaches, as well as focused, unfocused, and comprehensive strategies, the paper navigates through the theoretical frameworks guiding their application in L2 writing development. A key focus is on the frequency of WCF and its nuanced effects on learners' writing performance. By synthesizing empirical studies, the review elucidates the short-term and long-term impacts of corrective feedback on aspects such as accuracy, fluency, and complexity. Striking a balance between the amount and timing of corrective interventions emerges as crucial in optimizing the efficacy of WCF. The review also delves into the interplay between learner factors—such as proficiency level, motivation, and individual differences—and the reception and integration of corrective feedback. Understanding how these factors shape the impact of WCF contributes to tailoring instructional strategies to meet diverse learner needs. In conclusion, the paper offers practical insights for educators, highlighting the need for targeted WCF interventions aligned with learners' proficiency levels and motivational dynamics. By providing a nuanced exploration of WCF in L2 writing, this comprehensive review informs both research agendas and instructional practices, contributing to the ongoing enhancement of second language education